The difference between calcium ion levels in saliva before and after consuming red dragon fruit (Hylocereus polyrhizus) - Fakhrurrazi, Fakhrurrazi; Hakim, Rachmi Fanani; Reghina, Ayu Anisah (Universitas Padjadjaran, 2020)
Introduction: Saliva is a complex oral fluid that is secreted by the major and minor salivary glands which have a vital role in sustaining oral hard and soft tissues. The calcium ion is one of the inorganic components of saliva, which plays a vital role in maintaining the tooth enamel integrity through the remineralisation process. The compliance of calcium intake for the body and the enhancement of calcium ions in saliva can be affected by consumption of fruits that comprise lots of calcium. Consumption of fruit containing high calcium can increase buffer capacity, support remineralisation and prevent demineralisation. One of the fruits with rich calcium is red dragon fruit (Hylocereus polyrhizus). The purpose of this study was to analyse the difference between the salivary calcium ion level before and after consumption of red dragon fruit (Hylocereus polyrhizus) on the students of Faculty of Dentistry Syiah Kuala University batch 2017. Methods: This study was pre-experimental with one group pretest-posttest design. The number of subjects in this study was 32 people with one group pretest-posttest design. Saliva was collected by spitting method five times. Results: The average salivary calcium ion before consumption of red dragon fruit (Hylocereus polyrhizus) was 1.972, and the average value of salivary calcium ion after consumption of red dragon fruit (Hylocereus polyrhizus) was 2.378. Results of the statistical test using the paired t-test showed a significant difference of the salivary calcium ion before and after consumption of red dragon fruit (Hylocereus polyrhizus) with the p-value = 0.000 (p < 0.05). Conclusion: There is a difference of the salivary calcium ion level before and after consumption of red dragon fruit (Hylocereus polyrhizus).